РУРАЛНИ РАЗВОЈ У ФУНКЦИЈИ РАЗВОЈА ЛОКАЛНИХ ЗАЈЕДНИЦА - Сретен Јелић; Татјана Јовановић (Ekonomika Poljoprivrede (1979), 2011)
Rural development has signifcant part in development of rural comunities, especialy rural ares include 85% of Serbian teritory which have 42% of population. In the past few decades there is a trend of unbalanced rural development, which is particularly affected the rural areas which vary according to natural, economic, socio-political, cultural and demographic characteristics. There are signifcant differences in the development of rural communities - regions of Serbia, which produces the undisputed heterogeneity of rural society. It is necessary to reduce the existing differences in the level of development in which specifc role is to rural community development. In that sense changes in matrix work is presented as inevitable, but also a good way to deepen the understanding of today's rural communities, encourage local activities, rural policy, particularly with the help of research actions and multidisciplinary approach. Stressing the importance of multidimensionality of rural development, aim to illustrate the role of rural community development and research of new rural reality-based sources in the context of rural development in rural communities.